Utilization of Dry Cocoa Pod Husks as an Antioxidant-Rich Herbal Drink - Fitri, Ernarisa; Effendi, Effendi; Azra, Azmi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Cocoa (Theobroma cacao L) production in Indonesian has increased every year, therefore more cocoa pod husks are produced. Currently, the use of cocoa pod husks is still very limited, even most farmers only dump the pods and turn them into plantation waste which will later become new problems in the plantation environment, such as causing bad smell and spreading diseases to healthy cocoa. Even if there is use of cocoa pods, at this point it is only used for animal feed and compost. In fact, cacao pod husks contain flavonoids and phenolic compounds which have high levels of antioxidant activity which are very beneficial fot the health. Based on the results of the sample analysis test using the FTIR and XRF instrument, there are functional groups that contain antioxidants and based on the XRF test, the pods of cocoa also contain several minerals, including 60,69% potassium and 24,56 calcium. Antioxidants can prevent the activity of free radicals which are the main causes of degenerative diseases. Therefore, cacao pod husks are very useful for making herbal drinks by drying and pounding them into a homogeneous powder product.